Rede de atenção à saúde de pessoas com doenças crônicas não transmissíveis sob a perspectiva de seus articuladores - Martins, Ana Carolina Bertini (2018)
The Health Care Networks (HCN) in Brazil are essential for the coordination and integration of services, aiming the integrality and qualification of care, expanding strategies for health promotion, disease prevention and its complications. Between 2011 and 2012, five themes were agreed for these networks and one of them is the Attention to Non-Communicable Chronic Diseases (NCCD), which aims to provide fully attention to the health care for people with these diseases, which are associated with several causes. These diseases have a prognosis of long duration, they may also manifest disfigurement and generate disabilities. The basic care (BC) is a strategy of the Networks and the São Paulo State Department of Health created the program of articulators of basic care, which has the role of supporting, advising and developing actions for their qualification. The work becomes relevant because of the epidemiological picture of these diseases and their serious consequences for the affected individuals and their relatives, the increasement of the demand for care of these diseases in the health units and, consequently, a high cost for the country and municipalities. This work aimed to analyze the Network of Attention for People’s Health with Non-Communicable Chronic Diseases from the perspective of its articulators. The methodological approach was qualitative, with the use of a semi-structured script for interviews conducted in October 2017 with the four articulators working in the NCCD Network in two municipalities of medium size in the countryside of São Paulo State, with subsequent entirety transcription of the interviews and thematic categorical analysis , in which the goal is to identify, in the people’s speech, the meaning and values in relation to the object of study, taking into account the theoretical and methodological framework. The results found indicate weaknesses in the communication among the levels of attention, fragmentation of the care network, non-articulation of care lines and the need for more investments in basic care. The lack of human and financial resources has a direct impact on the implementation and functioning of this HCN. It is important to create strategies to sensitize the managers and shared management that best develop health actions, optimizing the work process, quality of care and life, both users and health workers.